Race and the Probability of Police Injury - Torres, Christopher E. (Race and social problems, 2021)
Although research finds that police are more apt to employ force against black criminal suspects, empirical evidence for this relationship is derived entirely from analyses that only account for factors associated with the police-citizen encounter. If racial disparities exist in how citizens view the police prior to the citizen-police encounter, then any observed nexus between a criminal suspect’s race and police use of force will suffer omitted variable bias. We indirectly test this thesis by examining whether a black criminal suspect has an enhanced proclivity to injure either a black or white police officer during an assault. Results show that black suspects are no more likely than white suspects to injure black or white police officers.